Meningkatkan Hasil Belajar Siswa Pada Pembelajaran IPS Materi Peran dan Kedudukan Anggota Dalam Keluarga Melalui Media Gambar di Kelas II SDN Cobodoe Kec. Tidore Timur Kota Tidore Kepulauan - Sufri Saleh (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to determine the student's ability to materialize the role and position of members in the family through picture media in social studies learning in grade 2 SDN Cobodoe, East Tidore District. In fact, teaching and learning activities are still experiencing various kinds of obstacles. The problem that arises is the lack of interest in students' learning which has an impact on their learning outcomes. conditions found in the learning process of Social Sciences in class II SDN Cobodoe, East Tidore district. The results of initial observations showed that students' understanding of certain materials was relatively low. The results of the study showed that the use of image media could increase the understanding of second grade students at SDN Cobodoe, East Tidore District in social studies learning about the position and role of members in the family. The data in the first cycle showed that the students' completeness was 13 out of 17 students or 76.5%. Mastery of students increased to 15 people or 88.3% in the second cycle.